Ketahanan Beton Mutu Tinggi Di Lingkungan asam - Pandiangan, Jaya Alexander; Olivia, Monita; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This research studies the durability of high strength concrete in acidic environment likes peat water and sulfuric acid solution. The high strength concrete will immersion in that both solution. After that, concrete will testing by mechanics and physical behavior likes compressive strength test, permeability test, porosity test, mass lost, visual changes, and acidic depth penetration by age of concrete. The main indictor of acidic solution in this reseach is point of hydrogen (pH) by solution. The range of pH by peat water are 4.00 â€“ 5.00 and sulfuric acid is is 5.00. The limited of compressive strength of the test spesimen is 50 MPa. This research gives the decrease of compressive strength by age in peat water immersion, whereas in sulfuric acid immersion this research shows the increase of compressive strength by age. The value of permeability of concrete in peat water immersion show the increase of permeability by age, but in sulfuric acid immersion the value of permeability increase in 28 days immersion and then decrease in 91 days immersion. Percent of porosity increase in 28 days immersion and decrease in 91 days immesion in peat water and sulfuric acid solution. Weight change test shows the dercrease of weight of the test speciment from all solution. The visual inspection changes test gives colouring changes onlyin test specimen in acidic solution and the result of depth penetration acid test is not showed the different result. Â Keyword: Peat water, sulfuric acid, high strength concrete, mass lost, compressive strength, acidic penetration, permeability, pH, porosity, visual inspection